A Pilot Study on the Willingness of Premarital Malays on Premarital Thalassaemia Screening - Nor Ezzati Nor Albashri; Asral Wirda Ahmad Asnawi; Rashidah Mohamed; Jameela Sathar; Ainoon Othman; Noor Fadzilah Zulkifli; Zetty Nadia Mohd Zain (Universiti Sains Malaysia, 2024)
Non-Indexed Publication